Investigation into aero-hydrodynamic surfaces for wing-in-ground effect vehicle design. - James, Daniel (Cranfield University, 2020)
This project focuses on developing the required knowledge and engineering data to be applied in the preliminary design of a Wing-in-Ground Effect vehicle. Three concurrent work programmes are carried out, covering experimental testing of a novel hull design, computational analysis of three wing profiles operating in ground effect, and an experimental programme to validate an unusual profile using an unconventional technique. This work is intended to produce a reliable database of 2D aerodynamic coefficients by establishing a robust methodology for numerical solution. A detailed range of heights above ground and angles of attack have been included, and the methodology can be easily applied to additional profiles in the future. A model wing was constructed and towed near the bottom of a water tank to replicate the physics and flow patterns of a wing immersed in an incompressible fluid moving over static ground. The selected profile was included in the computational work and the results of the two methods were compared. A hull model was designed and built, then towed at high speed to assess its potential performance in the take-off phase of WIG operation. As a radiussed-chined slender hull, it would also be suitable for waterborne operation at modest speed, leading to the possibility for a dual-purpose vehicle comfortable in air or water. Finally, a parametric geometry tool was developed to explore the design space and assess feasibility of various configurations. Relationships between primary components have been derived to allow sizing and positioning with corresponding powering estimates, to generate WIG conceptual designs.
Garry, Kevin P. - Associate Supervisor
Keywords: WIG; CFD; ICEM; tank testing; experiment; model; airfoil; wing; naval architecture